2004
DOI: 10.1111/j.1462-8902.2004.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sex hormone‐binding globulin and testosterone during weight loss and weight maintenance in abdominally obese men with the metabolic syndrome

Abstract: Rapid weight loss with successful weight maintenance in abdominally obese men with the metabolic syndrome brings about a sustained increase in fT levels. The dramatic increase in SHBG attenuated initially during weight maintenance but remained elevated. These findings may be important with regard to prevention of progressive metabolic decompensation and cardiovascular disease associated with obesity and the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
142
4
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(167 citation statements)
references
References 44 publications
15
142
4
6
Order By: Relevance
“…5 Weight loss was associated with a decrease in fasting insulin levels, increased mean plasma SHBG and total testosterone levels in both diabetic and nondiabetic intervention subjects, and free testosterone only in the diabetic men. This finding is concordant with that of other studies, which demonstrated improvements in total, 29 bioavailable 16 and free 29 testosterone levels after caloric restriction. For example, in a mixed group of diabetic and nondiabetic obese men, SHBG, total and free testosterone levels increased in response to a mean weight loss of 21 kg after 10 weeks of LCD.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…5 Weight loss was associated with a decrease in fasting insulin levels, increased mean plasma SHBG and total testosterone levels in both diabetic and nondiabetic intervention subjects, and free testosterone only in the diabetic men. This finding is concordant with that of other studies, which demonstrated improvements in total, 29 bioavailable 16 and free 29 testosterone levels after caloric restriction. For example, in a mixed group of diabetic and nondiabetic obese men, SHBG, total and free testosterone levels increased in response to a mean weight loss of 21 kg after 10 weeks of LCD.…”
Section: Discussionsupporting
confidence: 83%
“…16 Furthermore, in obese middle-aged men with the metabolic syndrome (B25% of whom were diabetic), weight loss of B14% induced by 9 weeks of LCD (800 kcal per day) increased total and free testosterone and SHBG levels. 29 In our study, the increase in total testosterone was correlated with the magnitude of weight loss and reduction in WC, possibly because of reduced insulin resistance; 5,30 moreover, aromatase activity in adipose tissue results in increased estradiol production, decreased pituitary gonadotropin production and reduction in testicular synthesis of testosterone. 31 In obese women, urinary symptoms and incontinence are improved by weight loss, 32 but there is a paucity of similar data in men.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, weight loss has been shown to improve testosterone levels, reducing fat mass and estrogen levels [135,136]. Modification may apply to changing prescription or nonprescription drug use and/or altering psychosocial factors [4].…”
Section: Step Care 3: Modifying Reversible Causesmentioning
confidence: 99%
“…Weight loss in obese men with metabolic syndrome has been shown to increase testosterone levels and reduce the complications of long-term hypogonadism. 33 …”
Section: Hypogonadismmentioning
confidence: 99%